The influence of roasting conditions on volatile flavour compounds in raw and roasted cashew kernels (Anacadium occidentale) grown in Nigeria - Olatidoye, Olawale Paul (Array, 2019)
The use of inappropriate temperature-time combinations during the roasting of nuts could lead to quality defects, such as burnt taste, short shelf-life, rancidity, and poor flavour. In this study, cashew kernels were roasted in a forced airflow-drying oven for 20, 40,and 60 min at 100, 120, 140, and 160°C. The productswere evaluated for volatile flavour compounds and the sensory evaluation of the roasted cashew kernelsat different roasting conditions. The volatile fraction was isolated using the combined steam distillation–extraction procedure and identified by gas chromatography–flame-ionization detection (GC-FID). The consumer acceptability test was carried out by 100 panellists using nine point hedonic scales to assess preferences for like or dislike, colour, taste, texture, flavour, and overall acceptability. It was found that there were significant differences in flavour compounds between the different conditions of roasting. Twenty-nine volatile compounds were identified in both fresh and roasted cashew kernels comprising five main classes, which consist of 12 hydrocarbons, eight aldehydes, four ketones, three alcohols,and one acid. The volatile compounds(mg/100g) ranged from 5.03x10-2to 1.20 (2-butanone), 7.46x10-6to 1.85 (hexanal), 8.91x10-6to 1.94 (acetone), 6.74x10-1to 2.24 (benzaldehyde). The amount of generated volatile compounds increased as the roasting temperature and time increased. The consumer acceptability test revealed that samples roasted for 40 or 60 min at 140°C produced the most acceptable product in terms of all the measured attributes. The study showed that the roasting conditions produced acceptable cashew kernels of desirable colour and superior flavour quality that enhance direct and commercial utilization.